1998
DOI: 10.1001/archneur.55.11.1460
|View full text |Cite
|
Sign up to set email alerts
|

Absence of an Apolipoprotein E ϵ4 Allele Is Associated With Increased Parietal Regional Cerebral Blood Flow Asymmetry in Alzheimer Disease

Abstract: Greater parietal rCBF asymmetry is involved in epsilon4- AD than in epsilon4+ AD. Lack of the epsilon4 allele may be associated with other (as yet undiscovered) genetic or environmental risk factors, which confer greater neuropathological asymmetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 34 publications
5
15
1
Order By: Relevance
“…Family history of AD has been shown to be a risk factor for AD beyond the eff ect of 4 alone [55] , which is one refl ection of the existence of additional genetic or environmental risk factors for AD. Samples of 4-negative AD patients are likely enriched for these factors [61] , which may in turn be associated with a form of AD conferring a later age of onset but equal or increased rates of clinical progression. Th us, the growing body of research examining phenotypic associations of ApoE 4 in AD samples is almost certainly confounded by an effective disequilibrium with other factors.…”
Section: Interpretation Of a Negative Eff Ect Of Apoe 4 On Ad Progressupporting
confidence: 65%
“…Family history of AD has been shown to be a risk factor for AD beyond the eff ect of 4 alone [55] , which is one refl ection of the existence of additional genetic or environmental risk factors for AD. Samples of 4-negative AD patients are likely enriched for these factors [61] , which may in turn be associated with a form of AD conferring a later age of onset but equal or increased rates of clinical progression. Th us, the growing body of research examining phenotypic associations of ApoE 4 in AD samples is almost certainly confounded by an effective disequilibrium with other factors.…”
Section: Interpretation Of a Negative Eff Ect Of Apoe 4 On Ad Progressupporting
confidence: 65%
“…[17][18][19] Furthermore, Hirono et al 20 provided evidence that the hypometabolism within the parietotemporal and medial temporal areas varies between early onset e3/e3 and e4/e4 carriers, but that these differences are lost for late onset patients. Together with previous research, the present results suggest that at the onset of AD cognitive symptoms, possible METglc differences between the ApoE genotype groups are no longer detectable within these mainly hypometabolic areas in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging studies may shed additional light on the association between ApoE e4 and psychotic manifestations of AD. One in vivo SPECT study has suggested that delusions in AD may be associated with hypoperfusion in the temporal lobes (Starkstein et al, 1994), and some (Lee et al, 2003) but not all (van Dyck et al, 1998) functional imaging studies have shown that AD patients who carry the e4 allele have reduced temporal lobe function. The structural MRI literature is more unified in showing greater medial temporal lobe atrophy in association with the e4 allele in AD (Lehtovirta et al, 1996b;Hashimoto et al, 2001;Basso et al, in press).…”
Section: Interpretation Of An Increased Risk Of Psychosis In Apoe E4 mentioning
confidence: 99%